Examining the influence of multiple performance characteristics on selection into a representative team in field hockey - Timmerman, E. A.; Savelsbergh, G. J. P.; Farrow, D. (High Ability Studies, 2021)
The aim of this study was to determine what kind of performance characteristics distinguish between different skill levels at different development stages in field hockey using a multi-dimensional testing battery. A total of 100 players identified as "talented" (51.0% girls) and 105 recreational level players (41.0% girls) divided over three age groups (U13/U15/U18) performed anthropometric, physical capacity, sport-specific technical skill and decision-making tests and completed self-regulation and sport history questionnaires. Gender specific multivariate analysis with playing level and age group as factors and age as a covariate were performed. Results revealed that experienced selectors and coaches select players for representative teams predominantly based on their dribbling skills, passing/hitting skills and speed and endurance. Furthermore, it is clear that selection for such a representative team is strongly influenced by maturational status and accumulated field hockey specific training hours. Interestingly, no differences were found between the self-regulatory skills of state and club level players for either gender. This study highlighted the performance characteristics deemed to be important by selectors and coaches and emphasized the need to consider the strong influence of maturational status and practice history when selecting "talented" players as these factors don`t translate to future sporting success.